PENGEMBANGAN MODEL SIMULASI BERBASIS MEDIA AUDIO VISUAL UNTUK KETERAMPILAN MERAKIT KOMPUTER DI SMK NEGERI 4 PONTIANAK - Dedi Setiyadi; Aunurrahman Aunurrahman; Dede Suratman (Universitas Tanjungpura, 2019)
AbstractThis research aims (1) to describe the preskripsi task of learning to assemble a computer. (2) design the look of the model of simulation-based audiovisual media skills to assemble a computer. (3) presents the relevant storyboard computer assemble a computer simulation model. (4) to understand the effectiveness of learning the skills to assemble the computers. Audio visual This development in research Method using the methods of research and development and modified with design model of the Dick and Carey. Assessment of the results of the validation of the media expert on average very good response, expert material on average very good designs and expert response average response very good showed learning materials-based model simulations and audiovisual computer assemble a computer meets eligibility criteria with a total average response from experts of very good. The earnings results of students before and after using media can be seen from the average value of the post-test students of 90 > 65 (KKM). Besides an increase in the value of the results of learning this can also be seen from the two paired samples t test showed the value t calculate more > t table (16.748 > 0, 8374). Besarnya the effectiveness of the use of simulation and model learning materials audio-visual assembles computers for learning computer Assembly of strong effect, then the results of the effectiveness of the intended learning gain in the category of high. This means it can be received well, tested, feasibility and effectiveness of learning that acquisition has high against the results of the learning at SMK Negeri 4 pontianak. Keywords: Development of a simulation model, Computer assemble a computer.